Analysis of reliability power supply intrusion and hold-up systems presented in the standard PN-EN 50131-1:2009 - Pędzierska Małgorzata (Journal of KONBiN, 2017)
The intrusion and hold-up system is one of the electronic security systems. The purpose of its application is to increase the level of safety for persons and property. This kind of solutions are used in all types of objects belonging to the critical infrastructure of the State. The article presents considerations for analysis reliability of intrusion and hold-up systems. Characterize them, taking into account the guidance contained in the standard “PN-EN50131-1:2009:Alarm systems-Intrusion and hold-up systems-part 1: System requirements”. Then performed an analysis of reliability that enable their comparison. In further research of this issue is planned to carry out similar analyses, but for systems of access control and video surveillance systems (also distributed structures).